2020
DOI: 10.3390/biom10081151
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Regulation of Mammalian Adult Neurogenesis: A Multifaceted Mechanism

Abstract: Adult neurogenesis—resulting in adult-generated functioning, integrated neurons—is still one of the most captivating research areas of neuroplasticity. The addition of new neurons in adulthood follows a seemingly consistent multi-step process. These neurogenic stages include proliferation, differentiation, migration, maturation/survival, and integration of new neurons into the existing neuronal network. Most studies assessing the impact of exogenous (e.g., restraint stress) or endogenous (e.g., neurotrophins) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 314 publications
(543 reference statements)
0
6
0
Order By: Relevance
“…First, overweight/obesity probably result in lower 5-HT levels [ 26 ] and, thus diminished the core subcortical/cortical region activity such as amygdala and medial prefrontal cortex, and reduce the activity of the underlying neural networks, which might impair the performance of EC [ 62 , 63 , 64 ]. Second, high 5-HT levels can exert direct effects on their receptors within the prefrontal cortex and hippocampus, and improve performance of EC at least in part via those mechanisms [ 65 ]. The results showed that serum 5-HT levels were responsible for 8.76% of the overweight/obesity associated with EC.…”
Section: Discussionmentioning
confidence: 99%
“…First, overweight/obesity probably result in lower 5-HT levels [ 26 ] and, thus diminished the core subcortical/cortical region activity such as amygdala and medial prefrontal cortex, and reduce the activity of the underlying neural networks, which might impair the performance of EC [ 62 , 63 , 64 ]. Second, high 5-HT levels can exert direct effects on their receptors within the prefrontal cortex and hippocampus, and improve performance of EC at least in part via those mechanisms [ 65 ]. The results showed that serum 5-HT levels were responsible for 8.76% of the overweight/obesity associated with EC.…”
Section: Discussionmentioning
confidence: 99%
“…86,87 In adult, the neurogenesis is partially controlled by sex hormones i.e., estradiol. 88,89 It has been reported that estradiol boosts neurogenesis correlating with cognitive improvement. 90,91 Moreover, estradiol can also ameliorate the neurodegenerative processes of Alzheimer's and Parkinson's diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Age, species, experience, exercise intensity and exposure frequency to sex hormones are proved to be a factor that determines adult-born neurogenesis. Also, plenty of hormones can lead to changes in various stages of the neural differentiation cascade [6,7,12,23,24]. They may have an effect on exercise-induced neurogenesis as well.…”
Section: Discussionmentioning
confidence: 99%
“…These studies discussed the sex hormones' significant role as neurogenic factors and multifaceted impact on different stages within the newborn neurons' maturation. [6][7][8][9][10] Androgen and estrogen are synthesized in both males and females, but in different volumes and play different roles by binding to their specific receptors (AR, ERα, ERβ). [11] Some researches contend that these sex hormone receptors can modulate neurogenesis as well [12].…”
Section: Introductionmentioning
confidence: 99%